2021
DOI: 10.37358/rc.20.12.8383
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Two-Phase Flow Patterns in a Vertical to Horizontal Bend Pipe Using Wire-Mesh Sensor

Abstract: The air-water two-phase flow plays an important role in many applications of industry fields. Usually, a 90-degree bend is used to connect pipes for changing the direction of flow which influences the two-phase flow pattern. In this paper, the effect of 90-degree bend under different ranges of gas and liquid superficial velocities on the two-phase flow patterns in the horizontal pipe located after the bend was experimentally investigated, and then results were presented and compared in a two-phase flow pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Some recorded void fractions are deleted due to some problem-related electricity issue and sensor themselves. The judgment of the classification of the two-phase patterns in the current tests isbased on the results of investigators in [1], [11], [15], [20]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recorded void fractions are deleted due to some problem-related electricity issue and sensor themselves. The judgment of the classification of the two-phase patterns in the current tests isbased on the results of investigators in [1], [11], [15], [20]…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the study clearly explains the flow regimes for gas-liquid flow using PDF the holding up of liquid in the time-series domain and PSD is used for flow identification in transparent inclined pipes,Abdulkareem [15]. A common technique was developed for the non-intrusive imaging technology and it was used to visualize the distribution of cross-sectional permittivity, for contents in a dielectric pipe regarding the capacitance of the measured data.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the volume of fluid (VOF) method, which flexibly and effectively handles complex interface configurations, is one of the most commonly and used application methods in numerical simulations of two-phase flow. , With the assistance of the VOF method, Gao et al numerically investigated the two-phase flow structures in a straight pipe, and their results agreed well with the flow regimes from experimental data presented by Mandhan et al Akhlaghi et al utilized the VOF model to simulate air–water intermittent slug and plug flow in a horizontal pipe and concluded that the ratio of the gas slug length to the liquid slug length increased with an increase in the gas superficial velocity. Qiao et al and Abdulkareem et al discussed the two-phase flow characteristics in a 90° vertical elbow pipe. Their results revealed that stratified–wavy flow was the dominant flow pattern in a horizontal pipe and that bubbly flow, plug flow, slug flow, and wavy–annular flow were also observed with an increase in the gas volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, many techniques were used in researches to identify the distribution of two-phase inside pipes at different orientations, like Wire-Mesh Sensor (WMS) [23,24], X-ray Tomography [25]. However, the pressure drops in different orientations using oil-gas two-phase flow were not presented sufficiently.…”
Section: Introductionmentioning
confidence: 99%